2018
DOI: 10.1038/s41598-018-36083-y
|View full text |Cite
|
Sign up to set email alerts
|

Loss of interneurons and disruption of perineuronal nets in the cerebral cortex following hypoxia-ischaemia in near-term fetal sheep

Abstract: Hypoxia-ischaemia (HI) in term infants is a common cause of brain injury and neurodevelopmental impairment. Development of gamma-aminobutyric acid (GABA)ergic circuitry in the cerebral cortex is a critical event in perinatal brain development. Perineuronal nets (PNNs) are specialised extracellular matrix structures that surround GABAergic interneurons, and are important for their function. Herein, we hypothesised that HI would reduce survival of cortical interneurons and disrupt PNNs in a near-term fetal sheep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 95 publications
(97 reference statements)
4
31
0
Order By: Relevance
“…In the present study, cerebral ischemia in near-term fetal sheep was associated with a pattern of parasagittal cortical damage after 7 days of recovery, which included a marked reduction in the survival of cortical GAD + , parvalbumin + , calretinin + , and calbindin + interneuron populations. These findings are broadly consistent with previous studies showing loss and disrupted development of interneurons in the cerebral cortex and subcortical grey matter following HI in preterm and term fetal sheep [17,[32][33][34][35] and neonatal rodents [36][37][38][39][40][41][42][43] and following ventilatory support in preterm baboons [44]. Although there are no comparable term human data, limited pathology and imaging studies in preterm infants have shown reductions in the numbers and complexity of cortical interneurons, refs [25,45] cortical interneuron migration, [7] interneuron neurogenesis, [46] and cortical GABAergic signaling [4].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, cerebral ischemia in near-term fetal sheep was associated with a pattern of parasagittal cortical damage after 7 days of recovery, which included a marked reduction in the survival of cortical GAD + , parvalbumin + , calretinin + , and calbindin + interneuron populations. These findings are broadly consistent with previous studies showing loss and disrupted development of interneurons in the cerebral cortex and subcortical grey matter following HI in preterm and term fetal sheep [17,[32][33][34][35] and neonatal rodents [36][37][38][39][40][41][42][43] and following ventilatory support in preterm baboons [44]. Although there are no comparable term human data, limited pathology and imaging studies in preterm infants have shown reductions in the numbers and complexity of cortical interneurons, refs [25,45] cortical interneuron migration, [7] interneuron neurogenesis, [46] and cortical GABAergic signaling [4].…”
Section: Discussionsupporting
confidence: 93%
“…There is increasing evidence that injury to cortical interneurons, including loss of PNNs and disruption of inhibitory interneuron circuits, is an important contributor to neurological disability following neonatal brain injury [17,25,26]. The present study demonstrates that blockade of connexin43 hemichannel opening with a mimetic peptide during early recovery from HI in term-equivalent fetal sheep improved survival of cortical GABAergic interneurons and prevented loss of cortical PNNs after 7 days of recovery.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It will be important to evaluate whether treatment with pharmacological MEK1/2 inhibitors or antioxidants during embryogenesis is capable of sustained restoration of CIN number in caMek1 , Slc32A1:Cre mice. PV-CIN sensitivity to MEK1 hyperactivation may not only be an important factor in RASopathy neuropathology, but could be a relevant mechanism in other conditions that involve indirect activation of ERK/MAPK signaling during embryogenesis, such as schizophrenia, Fragile X Syndrome, or prenatal stress (Fowke et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in preterm born infants, there is a widespread interneuronopathy as these cells are still migrating throughout the last trimester, a period of development disturbed by their early birth (91,92). Interneuron damage in neonatal stroke and HIE is limited to the region of frank cell loss (93,94). A role for HIE in preterm born infants is not conclusively supported (95), but oxygen variability is a likely contributor to injury (96).…”
Section: Neuroprotection and Repairmentioning
confidence: 99%